Die kleine House-Apotheke: Reception of the American, German and Polish Gregory House and Varied Translations of the Pronoun you - Urban, Anna (Research in Language, 2012)
Two audiovisual translations of the American hit medical drama, House M.D., German dubbing and Polish voiceover, and the analysis of translation strategies of the pronominal form of address you are the point of departure for choosing the right strategy for translation of the German book written by Michael Reufsteck and Jochen Stöckle Die kleine House-Apotheke. Ein Beipackzettel zur Kultserie which is the first German guide to the hit medical drama, providing unique insight into making of each episode of the first three series. The comparison of the two translation strategies - the German and the Polish one - shows that translation of the pronoun you determined the reception of the main protagonist. The reduced pronominal paradigm in English which does not distinguish between a formal and an informal address pronoun has created two different protagonists.